Medullary neuronal loss is not associated with α‐synuclein burden in multiple system atrophy. Issue 12 (15th September 2016) - Coon, Elizabeth A.; Schmeichel, Ann M.; Parisi, Joseph E.; Cykowski, Matthew D.; Low, Phillip A.; Benarroch, Eduardo E.
ABSTRACT: Background: Accumulation of α‐synuclein in multiple system atrophy (MSA) affects medullary autonomic and respiratory control areas, including the rostral ventrolateral medulla and raphe nuclei. Relative neuronal vulnerability and its relationship to α‐synuclein accumulation in these areas are unknown. The aim of this study was to determine the extent of loss of adrenergic neurons in the rostral ventrolateral medulla and serotonergic neurons in the ventrolateral medulla and raphe nuclei and its relationship with α‐synuclein accumulation. Methods: Medullary sections from 7 MSA and 6 control subjects were processed for tyrosine hydroxylase, tryptophan hydroxylase, and α‐synuclein immunoreactivity. Neuronal counts were performed stereologically, whereas α‐synuclein burden in oligodendrocytes and neurons was quantified using object detection density (area/mm2). Results: All MSA cases had orthostatic hypotension; 5 had laryngeal stridor. There was marked neuronal loss in the rostral ventrolateral medulla and medullary raphe in all cases. Most severely affected were tyrosine hydroxylase ventrolateral medulla (C1) neurons (83% reduction), followed by tryptophan hydroxylase neurons in the ventrolateral medulla (70%), raphe obscurus (56%), pallidus (57%), and magnus (47%). α‐Synuclein accumulation occurred predominantly as glial cytoplasmic inclusions with rare α‐synuclein accumulation occurring within the remaining neurons. Density of α‐synuclein did not correlate with neuronal loss in any of the areas analyzed, and there was no correlation between α‐synuclein density and disease duration for any regions of interest. Conclusions: These findings indicate that in MSA adrenergic neurons are more susceptible than serotonergic neurons in the medulla. Further, loss of medullary monoaminergic neurons may progress independently from α‐synuclein accumulation in MSA. © 2016 International Parkinson and Movement Disorder Society.